Risk factors and incidence of invasive bacterial infection in severe bronchiolitis: the RICOIB prospective study - Carmina Guitart; Carme Alejandre; Sara Bobillo-Perez; Monica Girona-Alarcon; Anna Sole-Ribalta; Francisco Jose Cambra; Monica Balaguer; Iolanda Jordan (BMC, 2022)
Abstract Background Bacterial infection (BI), both community-acquired (CA-BI) and hospital-acquired (HAI), might present as a severe complication in patients with bronchiolitis. This study aimed to describe BI in children with severe bronchiolitis, and to define risk factors for BI. Methods This was a prospective, descriptive study that included infants admitted to the pediatric intensive care unit (PICU) due to bronchiolitis between 2011 and 2017. The BROSJOD score was calculated to rate the severity of bronchiolitis. Results Inclusion of 675 patients, with a median age of 47 days (IQR 25-99). 175 (25.9%) patients developed BI, considered HAI in 36 (20.6%). Patients with BI had higher BROSJOD score, PRISM III, and required invasive mechanical ventilation and inotropic support more frequently (p < 0.001). BI was independently associated with BROSJOD higher than 12 (OR 2.092, 95%CI 1.168-3.748) CA-BI was associated to BROSJOD > 12 (OR 2.435, 95%CI 1.379-4.297) and bacterial co-infection (OR 2.294 95%CI 1.051-5.008). Concerning HAI, an independent association was shown with mechanical ventilation longer than 7 days (OR 5.139 95%CI 1.802-14.652). Infants with BI had longer PICU and hospital stay (p < 0.001), Mortality was higher in patients with HAI. Conclusions A quarter of infants with severe bronchiolitis developed BI. A BROSJOD > 12 may alert the presence of CA-BI, especially pneumonia. Patients with BI have higher morbidity and mortality.